Human Computer Interaction for Intelligent Systems - Pleva, Matúš; Liao, Yuan-Fu; Bours, Patrick (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint addresses the unique opportunities and challenges associated with human-computer interaction with intelligent systems. First, state-of-the-art reviews are presented about speech emotions, automatic spelling correction, and art usage in virtual reality. We encouraged authors to submit reports describing systems built for different languages and multilingual systems. The linguistic, emotional, prosodic, and dialogue aspects of speech communication are investigated. Special attention is given to sentiment and emotional analysis from text and speech. Speech audiometry, offline speech recognition, and text-independent speaker verification systems are elaborated. The rapidly growing domain of virtual reality applications is of interest both as an application domain in which new interfaces and interaction methods are needed and as a potential testbed for evaluating speech and other interface modalities.